Antimicrobial coating of spider silk to prevent bacterial attachment on silk surgical sutures. (November 2019) - Franco, Albina R.; Fernandes, Emanuel M.; Rodrigues, Márcia T.; Rodrigues, Fernando J.; Gomes, Manuela E.; Leonor, Isabel B.; Kaplan, David L.; Reis, Rui L.
Graphical abstract: Abstract: Microbial infections from post-surgery or other medical-related procedure is a serious health problem. Nowadays, the research is focused on the development of new drug-free materials with antibacterial properties to prevent or minimize the risk of infections. Spider silk is known for its unique biomechanical properties allied with biocompatibility. Recombinant DNA technology allows to bioengineering spider silk with antimicrobial peptides (AMP). Thus, our goal was to bioengineered spider silk proteins with AMP (6mer-HNP1) as an antibacterial drug-free coating for commercial silk sutures (Perma-Hand®) for decreasing bacterial infections. Perma-Hand® sutures were coated with 6mer-HNP1 by dip coating. In vitro tests, using human fetal lung fibroblasts (MRC5), showed that coated sutures sustained cell viability, and also, the contact with red blood cells (RBCs) demonstrate blood compatibility. Also, the coatings inhibited significantly the adherence and formation of biofilm, where sutures coated with 6mer-HNP1 produced a 1.5 log reduction of Methicillin-Resistant Staphylococcus aureus (MRSA) and a 2 log reduction of Escherichia coli ( E. coli ) compared to the uncoated Perma-Hand® suture. The mechanical properties of Perma-Hand® sutures were not affected by the presence of bioengineered spider silk proteins. Thus, the present work demonstrated that using spider silk drug-free coatings it is possible to improve the antibacterial properties of the commercial sutures. Furthermore, a new class of drug-free sutures for reducing post-implantation infections can be developed. Statement of Significance: Microbial infections from post-surgery or other medical-related procedure is a serious health problem. Developing new drug-free materials with antibacterial properties is an approach to prevent or minimize the risk of infections. Spider silk is known for its unique biomechanical properties allied with biocompatibility. Recombinant DNA technology allow to bioengineering spider silk with antimicrobial peptides (AMP). Our goal is bioengineered spider silk proteins with AMP as an antibacterial coating for silk sutures. The coatings showed exceptional antibacterial properties and maintained intrinsic mechanical features. In vitro studies showed a positive effect of the coated sutures on the cell behavior. With this new drug-free bioengineered spider silk coating is possible to develop a new class of drug-free sutures for reducing post-implantation infections.